The Activities Had Been Done by UNAND Students in Community Service Program 2023 in Nagari Batahan, West Pasaman - Syukri, Daimon; Santy Ayu Gultom, Eryka (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2023)
Community Service Program-Community Empowerment Learning (KKN-PPM) is one of the activities that must be carried out because it is one of the requirements for student graduation as an Andalas University student. This Community Service Program (KKN) is carried out one of which aims to advance education and student welfare at various levels. The programs carried out are socialization, introduction, and preparation of students to face college entrance exams, socialization to students in elementary schools about the impact of playing excessive cellphones and helping elementary school students in the preparation of Marching Band for the celebration of Independence Day on August 17, 2023. This initiative not only engages students in arts and culture, but also strengthens the spirit of patriotism and patriotism among students. Overall, the KKN program is an effective instrument in supporting student development in various aspects, making it one of the valuable assets in the world of Indonesian education, especially in Nagari Batahan, Ranah Batahan District, West Pasaman Regency.